Won't Get Fooled Again: A Supervised Machine Learning Approach for Screening Gasoline Cartels - Douglas Silveira; Silvinha Vasconcelos; Marcelo Resende; Daniel O. Cajueiro (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In this article, we combine machine learning techniques with statistical moments of the gasoline price distribution. By doing so, we aim to detect and predict cartels in the Brazilian retail market. In addition to the traditional variance screen, we evaluate how the standard deviation, coefficient of variation, skewness, and kurtosis can be useful features in identifying anti-competitive market behavior. We complement our discussion with the so-called confusion matrix and discuss the trade-offs related to false-positive and false-negative predictions. Our results show that in some cases, false-negative outcomes critically increase when the main objective is to minimize false-positive predictions. We offer a discussion regarding the pros and cons of our approach for antitrust authorities aiming at detecting and avoiding gasoline cartels.
Keywords: C21; C45; C52; K40; L40; L41; 330; cartel screens; price dynamics; fuel retail market; machine learning